2020
DOI: 10.1016/j.fuproc.2020.106476
|View full text |Cite|
|
Sign up to set email alerts
|

Gasoline from the bioliq® process: Production, characterization and performance

Abstract: Within the so-called bioliq® process, renewable carbon resources, especially agricultural residues, are converted to gasoline. The process chain comprises pyrolysis of the feedstocks, gasification to synthesis gas, gas cleaning and conversion of synthesis gas to dimethyl ether (DME) followed by conversion of DME to hydrocarbons. Construction of all process units has been completed now and the entire plant has been successfully operated in several campaigns. Thus, hundreds of liters of a new alternative gasolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The bioliq ® DTG raw gasoline is characterized by a high concentration of aromatics (approx. 75 wt.%), leading to a low proportion of light ends with boiling temperatures up to 150°C [23]. Such fuels are suitable for gasoline engines since the high aromatic concentration is accompanied by an increased octane number [10,22].…”
Section: Processes For the Production Of Synthetic Gasolinementioning
confidence: 99%
See 1 more Smart Citation
“…The bioliq ® DTG raw gasoline is characterized by a high concentration of aromatics (approx. 75 wt.%), leading to a low proportion of light ends with boiling temperatures up to 150°C [23]. Such fuels are suitable for gasoline engines since the high aromatic concentration is accompanied by an increased octane number [10,22].…”
Section: Processes For the Production Of Synthetic Gasolinementioning
confidence: 99%
“…Particulates and acid gas are subsequently removed in several gas purification stages to supply the refinery with high-quality, sulfur-free synthesis gas [30]. In the bioliq ® process, the synthesis gas is fed to a DTG synthesis to produce raw gasoline [23]. Detailed considerations of efficiency and production cost estimates of the bioliq ® process can be found in the work of Haro et al [28] and Henrich et al [33].…”
Section: Processes For the Production Of Synthetic Gasolinementioning
confidence: 99%
“…The design of the bioliq ® plant and the concept of the process were described before [10] and have not changed since. The raw gasoline feedstock used in this work was produced in the bioliq ® campaign in May 2019 and is designated as bioliq ® /100 2019 in the following.…”
Section: Further Development Of the Bioliq ® Product Refinementmentioning
confidence: 99%
“…To remove the high-boiling components, the bioliq ® /100 2019 raw gasoline was distilled in a laboratory-scale setup. Our previous work has shown that heavy aromatics are one of the main causes of emission formation during fuel combustion [10]. Thus, the conditions of product refinement were adjusted.…”
Section: Further Development Of the Bioliq ® Product Refinementmentioning
confidence: 99%
See 1 more Smart Citation